(untitled) (Research, Society and Development, 2022)
The growth in the number of people aged 60 and over is one of the most expressive demographic phenomena in Brazil. This reality requires a different look at all instances of care. The health of the elderly is a strategic area of ​​primary care, and the Ministry of Health created the Health Handbook for the Elderly (CSPI) to identify vulnerabilities and singularities of this disclosure and specific actions to minimize injuries. This study aimed to analyze the use of the CSPI by health professionals from the Basic Health Units of Teresina-PI. This is a descriptive, cross-sectional, approach study. A sample composed of 79 professionals working in Family Health Units. To maintain the Strategy data, an electronic system was used, consisting of questions of CS resources by the Health Strategy for the use of the Health Strategy. As a result, it was observed that 15.2% of professionals always use the booklet in their consultations; 44.4% point out as difficulties in the low use of the handbook by the entire health team; 46.8% said they were not made aware of the use of the CSPI by management and 68.3% were never received with training for the use of the CSPI. It was concluded that the CSPI has been used by health professionals, although it is not a very important instrument to qualify the care offered to the elderly in the SUS.